Accessing the Influence of Hess-Murray Law on Suspension Flow through Ramified Structures - Serrenho, Ana (2013)
The present study focuses on fluid flow and particle transport in symmetric T-shaped structures formed by tubes with circular and square cross-section. The performances of optimized structures (i.e., structures designed based on constructal allometric laws for minimum flow resistance) and not optimized structures were studied. Flow resistance and particle penetration efficiency were studied both for laminar and turbulent flow regimes, and for micrometer and submicrometer particles. Optimized structures have been proven to perform better for fluid flow but they have a similar performance for particle transport.